A preliminary study of dragonfly in Kampung Parit Tinggi, Negeri Sembilan / Syafiqah Amirah Sahawa - Sahawa, Syafiqah Amirah (Faculty of Applied Sciences, 2014)
The study of dragonfly diversity in Kampung Parit Tinggi, Negeri Sembilan was conducted within 16th September 2013 until 31st October 2013 with five samplings. The studies were conducted to determine the diversity and species composition of dragonflies and create a checklist of dragonflies’ species at Kampung Parit Tinggi, Negeri Sembilan. There were four method used in this study such as samples collection, killing method, preservation and identification method. A rich collection of 105 individuals belonging to 16 species from single family of Odonata was successfully identified at Kampung Parit Tinggi, Negeri Sembilan. Anisopterans (105 individuals) were found which Libellulidae (suborder Anisoptera) made up the most dominant family. Trithemis was the most common genera with 46 individuals. While the lowest genera were Acisoma (1 individual), Lathrecista (1 individual) and Rhyothemis (1 individual). Trithemis aurora was found to be the most abundant species recorded in this study with 46 individuals. The lowest individuals species caught were Acisoma panorpoides, Lathrecista asiatica, Neurothemis fulvia, Orthetrum glaucum and Rhyothemis phyllis with one individual each. Trithemis aurora and Pantala flavescens were the common species. Based on the ecological indexes, the value of diversity index (H’) was 1.95, Margalef’s index (R) was 7.42 and Evenness index (E) was 0.70. The ecological indexes showed that Kampung Parit Tinggi, Negeri Sembilan has high diversity index, richness index and evenness index.